Initial Tuning Sebagai Salah Satu Metode Pengoptimalan New Site Pada Jaringan Seluler Gsm (Studi Kasus Pada Area Kerja Pt. Sinergi Telecom Under Ericsson Network ) - Hesti Susilawati; Azis Wisnu Widhi Nugraha; Arif Widodo (Dinamika Rekayasa, 2007)
The development of new sites by telecommunication network operator, especially GSM network, purposes for more increase performance and give satisfy for consument. Performance of a site is most affecting for value of network quality totally. New site builded must be monitorized and optimized by its existing in order to can be more realible on serving society with the method that was mentioned “initial tuning activity”. On this method must be concerned some matter as like: application of accurate frequency for avoiding interference problem, creating neighbour relationship between ex isting site and new site, detection for faulth installation for arranging re-use frequency concept, setting accurate coverage, olso changing tilt angle for accurate main beam area. This arrangement must be conditioned on a new site that still “default”, so it can improve quality. On operator side, they have some criteria that must be passed by a new site. Initial tuning activity on Site Simpang RGM had been proved on passing  that site from recommended criteria, olso being totally indicated more increase pe rformance of network